Recommendations for coronavirus infection in rheumatic diseases treated with biologic therapy. Issue 109 (May 2020) - Ceribelli, Angela; Motta, Francesca; De Santis, Maria; Ansari, Aftab A.; Ridgway, William M.; Gershwin, M. Eric; Selmi, Carlo
Abstract: The Coronavirus-associated disease, that was first identified in 2019 in China (CoViD-19), is a pandemic caused by a bat-derived beta-coronavirus, named SARS-CoV2. It shares homology with SARS and MERS-CoV, responsible for past outbreaks in China and in Middle East. SARS-CoV2 spread from China where the first infections were described in December 2019 and is responsible for the respiratory symptoms that can lead to acute respiratory distress syndrome. A cytokine storm has been shown in patients who develop fatal complications, as observed in past coronavirus infections. The management includes ventilatory support and broad-spectrum antiviral drugs, empirically utilized, as a targeted therapy and vaccines have not been developed. Based upon our limited knowledge on the pathogenesis of CoViD-19, a potential role of some anti-rheumatic drugs may be hypothesized, acting as direct antivirals or targeting host immune response. Antimalarial drugs, commonly used in rheumatology, may alter the lysosomal proteases that mediates the viral entry into the cell and have demonstrated efficacy in improving the infection. Anti-IL-1 and anti-IL-6 may interfere with the cytokine storm in severe cases and use of tocilizumab has shown good outcomes in a small cohort. Baricitinib has both antiviral and anti-inflammatory properties. Checkpoints inhibitors such as anti-CD200 and anti-PD1 could have a role in the treatment of CoViD-19. Rheumatic disease patients taking immunosuppressive drugs should be recommended to maintain the chronic therapy, prevent infection by avoiding social contacts and pausing immunosuppressants in case of infection. National and international registries are being created to collect data on rheumatic patients with CoViD-19. Highlights: CoViD-19 is a pandemic caused by SARS-CoV2, that can lead to acute respiratory distress syndrome. Antimalarial drugs, anti-IL-1 and anti-IL-6 may be used in severe cases targeting the cytokine storm induced by CoViD-19. Recommendations for rheumatic disease patients include the prevention of infection by avoiding social contacts. Patients should also continue their ongoing therapy except in the case of overt infection.